Association between the herpes simplex virus major DNA-binding protein and alkaline nuclease. - Thomas, M S (1992)
Herpes simplex virus encodes seven proteins which have been shown to be both necessary and sufficient for in vitro replication of origin-containing plasmids. We have shown previously that one of these proteins, the major DNA-binding protein mDBP, forms a complex with alkaline nuclease, which is not one of the seven essential proteins. In this study, we have employed immunological reagents and a series of deletion mutants to investigate this complex further. We have determined the regions of mDBP which are important in the formation of this complex, and we have shown that the intranuclear locations of alkaline nuclease and major DNA-binding protein overlap.